2012
DOI: 10.1177/1461444812466715
|View full text |Cite
|
Sign up to set email alerts
|

Mobile voice communication and loneliness: Cell phone use and the social skills deficit hypothesis

Abstract: This study developed a research model of mobile voice communication on the basis of the social skills deficit hypothesis. In the model, poor social skills were related to less face-to-face and mobile voice communication, which was linked to greater loneliness. Structural equation modeling analyses of survey responses from 374 adults supported the social skills deficit hypothesis in that poor social skills were related to less involvement in face-to-face communication and greater loneliness. Also, as expected, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 52 publications
2
48
0
3
Order By: Relevance
“…Again, the study undertaken by Wu, Lo, Feng and Lo [19] reported that emotional and behavioral disorders/deficits of participant Taiwanese second and third graders decreased as their social skill acquisition level increased after they were trained in a social skills education program. Another study conducted in South Korea demonstrated that students without sufficient social skills experienced increased loneliness [20]. These results were in line with ours.…”
Section: Discussionsupporting
confidence: 91%
“…Again, the study undertaken by Wu, Lo, Feng and Lo [19] reported that emotional and behavioral disorders/deficits of participant Taiwanese second and third graders decreased as their social skill acquisition level increased after they were trained in a social skills education program. Another study conducted in South Korea demonstrated that students without sufficient social skills experienced increased loneliness [20]. These results were in line with ours.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study found that excessive users of smartphones experienced more depressive symptoms and difficulty in expressing emotions than the comparison group did [9]. In addition, a greater number of face-toface interactions was associated with lower levels of loneliness; however, more smartphone use was associated with greater loneliness [10].…”
Section: Discussionmentioning
confidence: 90%
“…Some studies have indicated that the excessive use of smartphones has negative effects on human psychology [9,10]. Excessive smartphone use reduces an individual's social implication in the real world and, as a consequence, his or her psychological well-being because it produces the kind of isolation, loneliness, and depression the individual seeks to ease by connecting to the Internet [11].…”
Section: Introductionmentioning
confidence: 99%
“…Intercept options to improve relationships: 1.82 (0.01)***; intercept options to lower expectations: 1.37 (0.01)***; threshold loneliness: 3.10 (0.67)***; threshold recently lonely: 2.45 (0.12)***; threshold persistently lonely: 1.91 (0.09); threshold recovered: 2.22 (0.11)*** competences as a prerequisite for developing satisfying relationships. For example, people lacking social competency may prefer texting to voice communication in using their mobile phone because it requires less emotional and cognitive commitment (Jin and Park 2013). To prevent or overcome loneliness social and emotional skills are required such as the ability to chat with people, to talk about sensitive matters, to listen to others, and to interpret signals (e.g., body language) that people transmit in conversations (DiTommaso et al 2003).…”
Section: How Coping Influences Lonelinessmentioning
confidence: 99%